Long-term comparison of pilot UASB and AnMBR systems treating domestic sewage at ambient temperatures. Issue 6 (December 2022) - Rattier, Maxime; Jimenez, Jose A.; Miller, Mark W.; Dhanasekar, Ashwin; Willis, John; Keller, Jürg; Batstone, Damien
Abstract: The upflow anaerobic sludge blanket (UASB) reactor and the anaerobic membrane bioreactor (AnMBR) are leading candidates for high-rate anaerobic treatment of domestic wastewater. The objective of this study was to perform a long-term comparison on the treatment of domestic sewage by the UASB and AnMBR systems at pilot scale at ambient temperature conditions and relate this to full-scale performance from a range of domestic strength UASB reactors. Analysis of overall operation indicated that the pilot reactor was more likely to be effective in removing solids (and less effective in soluble COD) than full-scale reactors, but that both had comparable performance ranges (i.e., from very effective, to very ineffective). Analyzing both UASB and AnMBR pilot plants treating the same wastewater, it can be concluded that both systems could achieve comparable performance (the UASB for very short periods), with COD removal efficiencies of more than 90%. However, the UASB could only achieve this performance for weeks at a time with good solids retention and long (>15 h) hydraulic retention time (HRT). This performance in general was not sustainable. For the UASB, the average COD removal at 15-h HRT was approximately 50%, with a significant reduction in performance as the hydraulic loading increased (which effectively reduced the HRT). Conversely, the AnMBR system produced exceptional COD removal at an HRT of 9 h. Considering this, the sustained volumetric methane production (per volume of reactor) was approximately 4 times that in the AnMBR than in the UASB system. Highlights: The UASB performance was affected by variation in hydraulic load. For the UASB, the average COD removal at 15-h HRT was approximately 50 %. The AnMBR was operated at an HRT of approximately 9 h with stable operation. The AnMBR produced exceptional COD removal of approximately 85% at an HRT of 9 h. The main disadvantage of the AnMBR was the energy cost of membrane fouling control.